2009
DOI: 10.1002/jor.20768
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute tensile loading on gender‐specific tendon structural and mechanical properties

Abstract: Stretching is commonly used prior to exercise, as it is thought to reduce the risk of injury, and it is also used in the preconditioning of tendon grafts. As tendon properties have been shown to be different between genders, it is proposed that stretching will differentially affect the structure. Here we examine the effect of acute stretch on the mechanical properties of both male and female medial gastrocnemius tendon. Female [20 years AE 1 (SEM), n ¼ 17] and male (22 years AE 1, n ¼ 18) subjects underwent a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
74
5
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 35 publications
(50 reference statements)
8
74
5
2
Order By: Relevance
“…Effect of exercise on Achilles free tendon transverse morphology at rest Consistent with previous in vivo studies, we found no change in regional CSA measured at rest immediately after exercise (Burgess et al, 2009;Farris et al, 2012;Lichtwark et al, 2013;Obst et al, 2015;Ooi et al, 2015). While our results did show a small but consistent reduction in CSA across all measurement regions (∼7%), post hoc comparisons failed to reveal any significant differences between time points at any of the tendon regions.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Effect of exercise on Achilles free tendon transverse morphology at rest Consistent with previous in vivo studies, we found no change in regional CSA measured at rest immediately after exercise (Burgess et al, 2009;Farris et al, 2012;Lichtwark et al, 2013;Obst et al, 2015;Ooi et al, 2015). While our results did show a small but consistent reduction in CSA across all measurement regions (∼7%), post hoc comparisons failed to reveal any significant differences between time points at any of the tendon regions.…”
supporting
confidence: 89%
“…These short-term reductions in AP diameter after exercise have been suggested to reflect fluid exudation from the tendon core to the peri-tendinous space as a result of the creation of positive hydrostatic pressure within the tendon when tendon fibres stretch and pack under tensile load (Grigg et al, 2009;Hannafin and Arnoczky, 1994). While in vitro studies demonstrate load-dependent changes in fluid content and tendon dimensions in response to repeated loading (Hannafin and Arnoczky, 1994;Helmer et al, 2006;Wellen et al, 2005), in vivo studies of the human Achilles tendon report mixed findings with respect to exercise-induced changes in tendon volume (Pingel et al, 2013a, b;Shalabi et al, 2004;Syha et al, 2013) and crosssectional area (CSA) (Burgess et al, 2009;Farris et al, 2012;Neves et al, 2014;Ooi et al, 2015); discrepancies that may reflect different exercise interventions, populations or imaging methods used to assess tendon morphology. It is also currently unclear whether changes in transverse morphology and strain following exercise are uniformly distributed across the length of the tendon, occur along the medio-lateral (ML) diameter, related to changes in longitudinal deformation, or are more pronounced under tensile load.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results significantly differ from their study, for which several possible reasons can be proposed. It has been shown that gender influences the mechanical properties of soft tissues, indicating that tendon stiffness can be up to 37% lower in female tendons compared to males [2,13,18]. Hauch et al, whose donors were 80% male, measured higher stiffness and ultimate load values compared to our study, in which the donors were 80% female.…”
Section: Discussioncontrasting
confidence: 64%
“…Although tendon stiffness and sometimes cross sectional area (CSA) is increased after several weeks of resistance training a decrease in stiffness has been reported in Achilles (Burgess et al 2009;Kay and Blazevich 2009;Kubo et al 2002) and patellar tendons (Kubo et al 2001a, b;Yin et al 2014) after a single session of resistive and stretching exercises.…”
Section: Introductionmentioning
confidence: 99%